Stable Nuclei of Nucleoprotein Filament and High ssDNA Binding Affinity Contribute to Enhanced RecA E38K Recombinase Activity - Lu, Chih-Hao (Sci Rep, 2017)
RecA plays central roles in the homologous recombination to repair double-stranded DNA break damage in E. coli. A previously identified recA strain surviving high doses of UV radiation includes a dominant RecA E38K mutation. Using single-molecule experiments, we showed that the RecA E38K variant protein assembles nucleoprotein filaments more rapidly than the wild-type RecA. We also used a single-molecule fluorescence resonance energy transfer (smFRET) experiment to compare the nucleation cluster dynamics of wild-type RecA and RecA E38K mutants on various short ssDNA substrates. At shorter ssDNA, nucleation clusters of RecA E38K form dynamically, while only few were seen in wild-type RecA. RecA E38K also forms stable nuclei by specifically lowering the dissociation rate constant, k (d). These observations provide evidence that greater nuclei stability and higher ssDNA binding affinity contribute to the observed enhanced recombination activity of the RecA E38K mutant. Given that assembly of RecA nucleoprotein filaments is the first committed step in recombinational repair processes, enhancement at this step gives rise to a more efficient recombinase.